Pengaruh Harga dan Citra Perusahaan Terhadap Keputusan Pembelian Jasa Wedding Planner CV. Showbitz Mitra Andalan Medan - Silitonga, Grace Novelina; Rangkuti, Agus Edy (Civiliza Publishing, 2024)
Price is the amount of value or money exchanged by consumers to obtain or use a product or service. Corporate image is a person's perception of an organization's image and these perceptions are created through all the senses of sight, hearing, smell, touch, taste, and feeling experienced through the use of products, consumer services, commercial environments and corporate communications. This study aims to analyze the effect of price and corporate image on the decision to purchase wedding planner services at CV Showbitz Mitra Andalan. The research method used is a quantitative method with data collection through a questionnaire with a sample of 34 respondents using the saturated sample technique. The data obtained were analyzed using SmartPLS. The results of this study indicate that price has a positive but not significant effect partially on the decision to purchase services of (0.36). Corporate image has a positive and significant effect partially on the decision to purchase services of (0.52). Simultaneously, price and corporate image have a positive effect on the decision to purchase by (0,57).